Avaliação de produtos naturais no controle de biofilmes formados em sistema dinâmico - Viana, Marcelino Gevilbergue (2009)
The biofilms microbial forms of association are responsible for generating, accelerating and / or induce the process of corrosion. The damage generated in the petroleum industry for this type of corrosion is significatives, representing major investment for your control. The aim of this study was to evaluate such tests antibiograms the effects of extracts of Jatropha curcas and essential oil of Lippia gracilis Schauer on microrganisms isolated from water samples and, thereafter, select the most effective natural product for further evaluation of biofilms formed in dynamic system. Extracts of J. curcas were not efficient on the complete inhibition of microbial growth in tests type antibiogram, and essential oil of L. gracilis Schauer most effective and determined for the other tests. A standard concentration of essential oil of 20 μL was chosen and established for the evaluation of the biofilms and the rate of corrosion. The biocide effect was determined by microbial counts of five types of microorganisms: aerobic bacteria, precipitating iron, total anaerobic, sulphate reducers (BRS) and fungi. The rate of corrosion was measured by loss of mass. Molecular identification and scanning electron microscopy (SEM) were performed. The data showed reduction to zero of the most probable number (MPN) of bacteria precipitating iron and BRS from 115 and 113 minutes of contact, respectively. There was also inhibited in fungi, reducing to zero the rate of colony-forming units (CFU) from 74 minutes of exposure. However, for aerobic and anaerobic bacteria there was no significant difference in the time of exposure to the essential oil, remaining constant. The rate of corrosion was also influenced by the presence of oil. The essential oil of L. gracilis was shown to be potentially effective